Kontekstual ANALISIS KEBUTUHAN BAHAN AJAR KONTEKSTUAL PADA PELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Sulis Wahyu Ningsih, Nurul Maharini, Fat-thahillah Candra At-Toriq, Hermawan Wahyu Setiadi (STKIP Subang, 2025)
This study aims to analyze the needs for the development of contextual teaching materials in Indonesian language subjects at SD Muhammadiyah Ambarbinangun. The background problem is the low productive writing skills (descriptive and procedural texts) of students, triggered by generic teaching materials, thus failing to build connections between linguistic concepts and students' real-life experiences. This descriptive qualitative research involved 4 classroom teachers and 5 student representatives from grades IV and V. Data were collected through in-depth interviews, direct observation of learning activities, and literature study. The results of the study found a significant contextual gap, where students experienced an ideational block due to the lack of local content and environment-based Modeling, while teachers struggled to implement Contextual Teaching and Learning (CTL) without explicit instructional guidelines. In conclusion, there is a high urgency to develop a structured Contextual Teaching and Learning Module based on local content as an intervention solution to bridge the contextual gap, thereby improving students' authentic writing skills and critical thinking abilities. Keywords: Contextual Teaching Materials, Contextual Teaching and Learning (CTL), Local Content